Comparison of different school screening procedures - Lanu W.A (Journal of All India Institute of Speech and Hearing, 1970)
In recent years, investigators like House and Glorig 1957, ASHA, 1975, Northern and Downs, 1978 etc., in the field of hearing screening and hearing conservationhave suggested procedure that will more quickly and efficiently screen large number of subjects. Since there is no standard or recommended school screening procedure in India it is necessary to evaluate and compare some of the commonly used procedures to choose the one that is suited to Indian conditions.